1980
DOI: 10.1103/physrevlett.45.1371
|View full text |Cite
|
Sign up to set email alerts
|

Clusters and Tubes in Multiparticle Production from Nuclear Targets

Abstract: Recent data on backward pion production in 0.8-4.89-GeV proton-nucleus collisions are analyzed within the scope of models where target nucleons react collectively. It is shown that the nuclear-size dependence in data is a sensitive probe of the effective target mass. The experimental results hint at a synthesis of the cluster ("fluctuon") model and the collective tube model. PACS numbers: 13.85. Kf, 12.40.Cc, 25.40.Rb, 24.10.Dp In a recent Lawrence Berkeley Laboratory experiment Schroeder etal. 1 measured t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…During de-excitation, pions are emitted in a manner similar to that in thermal models. This conclusion is also consistent with the model of Fredriksson [15] , in which the incident nucleons interact collectively with all matter within 1 fm (in the rest frame) at the line of collision. It is obvious from Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…During de-excitation, pions are emitted in a manner similar to that in thermal models. This conclusion is also consistent with the model of Fredriksson [15] , in which the incident nucleons interact collectively with all matter within 1 fm (in the rest frame) at the line of collision. It is obvious from Fig.…”
Section: Resultssupporting
confidence: 90%
“…They argued that the simple Fermi motion of the nucleons in the nucleus could not account for such backward production and stated that the dominant mechanism for producing such hadrons was the interaction between the incident nucleon and multi-nucleon clusters in the target, referring to this mechanism as cumulative production. Fredriksson [15] supported the model in which the nucleon interacts collectively with all matter within 1 fm in its rest frame at the time of collision. The LBL data [2,8] supported a model called the "effective target model" [4] .…”
Section: Introductionmentioning
confidence: 91%
“…The emission in the backward hemisphere (BHS) is restricted. Pion emission beyond the kinematic limits at θ lab 90°was suggested to be due to target fragmentation system, regarding the limiting fragmentation hypothesis [11][12][13][14][15]. This was investigated and confirmed by our lab group [10,[16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 55%
“…The intercept values are parameterized as a function of the projectile mass number in figure 9. The allometric fitting in figure 9 is presented by the power law equation (13). It has χ 2 /dof=0.…”
mentioning
confidence: 99%
“…Accordingly, the pion production was investigated according to the directional zone of emission. Various experimental and theoretical studies had been focused at Dubna and Lawrence Berkeley National Laboratory (LBNL) to solve the problem [1][2][3][4]. El-Nadi et al [5][6][7] showed that the backward emitted pion multiplicity is strongly correlated with the target fragment multiplicity at Dubna energy.…”
Section: Introductionmentioning
confidence: 99%